Basic Jawi learning and writing using augmented reality application for primary school standard one students syllabus / Siti Shafida Sharifuddin - Sharifuddin, Siti Shafida (2019)
Jawi Mobile Application with Augmented Reality is an application for standard one students to learn basic alphabet of Jawi. This application with augmented reality to help the students more understandings and fun during learning Jawi. It helps the students in practices Jawi in the study. The objectives of this project are to develop Jawi augmented reality application as teaching material for primary school standard one students and to evaluate the usability of Jawi augmented reality application towards standard one students. Research methodology used is ADDIE model. There are thirty students that were tested to use this application using usability testing. The result has shown that the students were satisfied with the application. Augmented Reality is something new that can attract the interest of students in their education. In the future work, there are few recommendation for this project. The application can be improve by provide more language to be use, adding more animation features and implemented in virtual reality to attract the standard one school students.